The role of pharmaceutical care in pediatric oncology (Research, Society and Development, 2023)
In the cancer patient care service, the pharmacist provides personalized advice and supervises the treatment. Thus, the objective of the present study was to discuss the performance of the pharmacy professional in a multidisciplinary team in the treatment of pediatric cancer patients. The present study is a qualitative, explanatory and deductive research based on a bibliographical review, of the narrative type, addressing the knowledge of pharmaceutical professionals about the role of pharmaceutical care in pediatric oncology. The present study is a qualitative, explanatory and deductive research based on a bibliographical review, of the narrative type, addressing the knowledge of pharmaceutical professionals about the role of pharmaceutical care in pediatric oncology. For the effectiveness of cancer treatment, in addition to antineoplastics, therapy requires drugs such as antiemetics, analgesics, antimicrobials, among others, which minimize the adverse effects of chemotherapy and radiotherapy, as well as the signs and symptoms arising from the disease. Dispensing is an important process, as it provides information about the prescribed treatment, allowing the patient to understand the medications they will use, since the lack of guidance to the patient can cause poor adherence, undesirable effects, therapeutic failure, adverse effects and interfere in the patient's evolution. In summary, pharmaceutical assistance is a fundamental pillar in the field of pediatric oncology. Pharmaceutical professionals specialized in this area have a multifaceted role, working from the selection and preparation of medicines to direct support to patients and their families.